Perception, Knowledge and Attitude About Human Papillomavirus Infection Among Adult Female in Ciranjang, West Java - Pangaribuan, Santa Maria; Barakah, Josephine Tahasy (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Cervical cancer is caused by human papillomavirus (HPV) but it can be reduced by HPV infection.The aimed of this study was to explore perception and knowledge about HPV, cervical cancer andHPV vaccine in Ciranjang West Java, Indonesia. This was a cross sectional study of 90 adult femalein Ciranjang, West Java, Indonesia. A 31 item self-report questionnaire was completed in this study.The reliability of this tool was assessed using Cronbach’s alpa (0.86) and the Kaiser-Meyer-Olkinvalue was 0.704. A total of 90 questionnaire were distributed, completed and analyzed. Only 42(46.7%), 69 (76.7%) and 69 (76.7%) of adult female had ever heard of HPV infection, cervical cancerand HPV vaccine respectively. Only 13 (14.4%) knew that HPV can cause herpes and 28 (31.3%)knew that HPV can cause genital warts. Of the 44 adult female knew that there is a vaccine beingdeveloped to prevent HPV infection. Generally, the perception, knowledge and attitude about HPVamong adult female were low. There is a need for health promotion to improve knowledge,perception and HPV vaccine.